Sodium Nitrite Effects on Some Blood and Biochemical Parameters in Glutathione Treated Male Rats - Huda Khassaf (Basrah Journal of Veterinary Research)
In industrial food production, food preservatives like sodium nitrite are used more frequently. The use of some food preservatives has been linked to teratogenic and carcinogenic effects. In order to investigate the effects of food additives such as sorbitol and natural antioxidant substances on rats forty adult male albino rats, approximately one month and a half were divided into four groups as follows, Group 1 serves as control group supplement with (Nacl 0.9% normal saline).Group 2 received a sodium nitrite supplement (30 mg/kg BW), group 3 supplemented initially with sodium nitrite and glutathione and group 4 supplemented with glutathione (6.42 mg/kg BW). A variety of parameters were measured, including the number of red and white blood cells (RBCs & WBCs), hemoglobin (Hb) level, hematocrit (Hct) value, glucose level, and serum alanine transaminase and aspartate transaminase (ALT & AST) activity analysis.  The results clearly showed that (RBCs), (Hb) concentration, and (Hct) value of rats treated with sodium nitrite for two months exhibit significant decrease when compared to the control and treated groups, rats given with either glutathione alone or glutathione plus sodium nitrite showed significant decrease in their serum glucose levels and there was discernible elevation in the serum activity of AST and ALT in rats treated with glutathione alone. Rats treated with sodium nitrite showed a substantial decrease (P< 0.05) in AST activity after 2months when compared with the control group, whereas significant increase (P< 0.05) in ALT activity were detected after 2months  . These results indicate the harmful effects of using artificial supplements and colorings and also prove the improving effect of glutathione. Due to the potentially harmful effects of food additives, it is advised that the use of S. N. as an additive be kept to a minimum. Gluathione, on the other hand, can prevent toxic effects.